The Territorial Trap and The Problem of Non-territorialized Groups - Karman, Mireille Marcia (Global: Jurnal Politik Internasional, 2016)
This article aims to argue that territory is ahistorical concept rather than a constant one in explaining political conception of state and other political entities. Referring to liberalism and political realism, territory has been one of the core concepts in the study of political science. This paper will then elaborate the concept of territoriality and its problem in the era of globalization, which will also describe the existence of territory of non-state actor in private and public sphere. At the end of this article, I will outline the possibility to have a different reaction against the threat of non-state actor when the notion of territory is not taken for granted anymore.